George of the jungle [videorecording (DVD)] - Weisman, Sam; Fraser, Brendan, 1968-; Mann, Leslie, 1972-; Church, Thomas Haden; Taylor, Holland; Roundtree, Richard, 1942-; Cleese, John (Walt Disney Home Video : Distributed by Buena Vista Home Entertainment, 2000)
George is a buff and lovable klutz who saves his animal friends from poachers.